New Record of A Freshwater Prawn Macrobrachium sundaicum in Selat Panjang Island, Riau Province, Indonesia - Purnamasari, Lora; Perwitasari-Farajallah, Dyah; Wowor, Daisy; Farajallah, Achmad; Annawaty, Annawaty (Universitas Gadjah Mada, 2024)
A freshwater prawn M. sundaicum, is an obligate species to acidic peat swamp. Up to the present, M. Sundaicum has only been reported in the West Kalimantan, the Riau Archipelago, and Jambi Provinces in Indonesia. The aim of this research is to determine the distribution and habitat preferences of peat swamp prawn in Selat Panjang Island, Riau Province, Indonesia. The samples were collected in seven peat swamp rivers by hand net. The study yielded one hundred specimens. The acidic peat swamp is a perfect habitat for M. sundaicum. This study provided the basic information about peat swamp prawn in Selat Panjang Island, especially their distribution and habitat preferences.